A Case of Linezolid Induced Toxicity. (April 2020) - Tobias, Philip E.; Varughese, Christy A.; Hanson, Amy P.; Gurnani, Payal K.
Adverse effects of linezolid are typically limited to diarrhea, nausea, and headache when shorter durations are used; however, as extended durations of linezolid therapy are increasingly more common, additional monitoring parameters should be considered in these patients. We describe a unique case of hypoglycemia, lactic acidosis, and pancreatitis related to an extended duration of linezolid therapy. A 52-year-old woman presented with altered mental status, abdominal pain, and hypotension following six weeks of linezolid and ertapenem therapy. Laboratory data revealed an initial blood glucose of 40 mg/dL and metabolic acidosis secondary to lactic acidosis. Finally, her abdominal pain on admission was likely related to an enlarged pancreas noted on computed tomography of her abdomen. Due to suspected linezolid toxicity, the patient received two intermittent hemodialysis sessions to remove linezolid and correct the metabolic acidosis. Given limited data on long-term monitoring of patients receiving extended durations of linezolid therapy, we suggest periodic monitoring of lactate, arterial blood gas, and blood glucose. If patients present with this triad of symptoms secondary to linezolid therapy, adverse effects should be treated with dextrose and intravenous thiamine while reserving hemodialysis for those with metabolic acidosis refractory to thiamine.